TAHAPAN BERDUKA PADA KLIEN DENGAN DIABETES MELLITUS TIPE 2 - Minarti Minarti (JURNAL PENELITIAN KESEHATAN, 2018)
Diagnosis and treatment of clients suffering from Diabetes Mellitus leads to changes or imbalances that include the client's biology, psychology, social and spiritual impacts on family life. Prevalence of Diabetes Mellitus clients has an upward trend of 1.1% in 2007 to 1.5% in 2013. The prevalence of Diabetes Mellitus based on a doctor or symptom diagnosis in 2013 was 2.1%. The incidence of Diabetes Mellitus clients in Surabaya Municipality is 5.10% with Diabetes Mellitus with age more than 40 years. The purpose of this study is to identify the stage of grief at Type 2 Diabetes Mellitus clients. The research design used is descriptive research. Sampling technique used purposive sampling. Population taken is all client of Diabetes Mellitus residing in RW 02 Village Kemayoran Surabaya a number of 42 client. Sample size according to research criteria as many as 20 people. The variables in this study were the grieving stages of Diabetes Mellitus type 2 clients. The results showed that the grieving stages of Diabetes Mellitus clients were known almost entirely (90%) at the low acceptance stage of the disease, followed by rejecting high category 80% and low bargaining 80 %. Also found depression stage in high category 60% and angry in low category 65%. A person diagnosed with a particular disease can cause actual and potential changes and problems in various aspects. Problems that arise can be physical and psychological aspects that occur fluctuate from the refuse, anger, bargaining, depression and accept. Suggested in implementing nursing intervention on client Diabetes Mellitus should be in accordance with the stage of grief experienced by the client.